Forecasting and Responsible Innovation: A Book Review - Moniz, António Brandão (Frontiers in Sociology, 2022)
The new book edited by Rodríguez and colleagues focuses on the topic of forecasting and responsible innovation. The original title is “Anticipación e Innovación Responsible: La construcción de futuros alternativos para la ciencia y la tecnologia” and was published by Biblioteca Nueva, Madrid. Along this text, I will be using the term forecasting instead of anticipation to consider the Spanish concept of “anticipación”. Both concepts are usually applied to “the act of looking forward” (Merriam-Webster dictionary) or “the act of expecting or foreseeing something; expectation or presentiment” (Farlex dictionary). The concept of forecasting is usually used in scientific debate as ““the process of making predictions based on past and present data and most commonly by analysis of trends” (Wikipedia). Glenn expresses this definition well by saying that “studying the future is not simply economic projections or sociological analysis or technological forecasting, but a multi-disciplinary examination of change in all major areas of life to find the interacting dynamics that are creating the next age” (Glenn 1994). The concept has been developed mainly by Armstrong (2001) and followed by Farrukh & Holgado (2020), Schnaars (2009) or Marinakis (2012), among others. The editors are researchers from the Universities of Basque Country and Mondragon. Although, still published just in Spanish, it is an important contribution to the social sciences and philosophy of sciences on the analysis of alternative socio-technical futures with strong ethical principles, which becomes as an innovative approach among systematic debate based on biased perspectives and vested interest opinion making.